ANALISIS PENGARUH KETERBUKAAN PERDAGANGAN DAN INVESTASI ASING TERHADAP PDB INDONESIA - Premana Jati, Arya Rozaq; Afridi, Kin Ali; Tri Hapsari, Maria Olivia Tita; Maharany, Destina; Indriasari, Felda; Datubara, Kesia; Raysharie, Puput Iswandyah (STIE Jambatan Bulan, 2025)
The purpose of this study is to determine the significance level of the impact of foreign investment and trade openness on Indonesia's GDP. This study utilizes a quantitative methodology, with the help of time series-based secondary data. information obtained from the national statistical office. The population of Indonesia is equivalent to GDP and the level of foreign investment. The period covered by the sample is January 2019-December 2023. In this study, SPSS 29 was used to process the data, and a multiple regression model was employed. The findings of the study lead to the conclusion that the data is normally organized and there are no abnormalities of the classical assumptions of heteroscedasticity, multicollinearity and autocorrelation. This study shows that foreign investment is insignificant and negatively affects GDP, while trade openness is significant and positively affects GDP